Análisis del proceso de comunicación en un proceso de mediación de conflictos con una pareja de separados, basado en la teoría de la acción comunicativa de Habermas y el modelo relacional simbólico (2010)
The present includes a case study of a family mediation process with a separated couple in a Judiciary Consultant service of the Rosario University at Bogotá, Colombia. Its purpose was to analyze the type of communication dialogues that occurred during the mediation process, based on Jurgen Habermas Action Communication Theory and the Symbolic Relationship Model of Mediation (MRS) developed by the School of Family Studies of the Université Cattólica del Sacro Cuore di Milano. The core of the conflict mediation process is centered upon the comprehension of bonding in a couple, family or community members, as well as the symbolic meaning that act as regulators of the relationship. The structure of the bonding between a couple, together with the basic gender differences between being a man or a woman, and the task of providing for the generations within the conscience of nurturing, is basic to guarantee the maintenance of the parental task for their offspring after the rupture of the marriage bonding.